(untitled) (Principles and Practice of Clinical Research, 2023)
Introduction: Many inflammatory conditions directly impact the skin through different pathways, the understanding of which should be a priority to develop new medications to treat patients suffering from these conditions. Some studies have demonstrated the anti-inflammatory properties of Hypericum perforatum (HP), but no previous systematic reviews have described all the mechanisms by which topical HP may act on inflammation. Therefore, the purpose of this review was to assess the effects of topical HP on inflammatory markers in inflammatory skin conditions or models involving epithelial cells that have been described so far. Methods: The databases PubMed, Scopus, Research4Life (HINARI), and SciELO were used to retrieve experimental and observational studies, from inception to September 25, 2022, reporting the effects of HP on inflammatory markers in inflammatory skin conditions or models involving epithelial cells. We used the following keywords: Hypericum perforatum, H. perforatum, Saint John’s wort, hypericin, hyperforin, inflammation, pro-inflammatory, inflammatory, inflammatory biomarkers, chemokine, prostaglandin, inflammation mediators, TNF, and tumor necrosis factor. Results: From 348 articles screened, 11 were selected based on inclusion and exclusion criteria: two in vitro studies, eight animal studies, and one human pilot trial. A reduction in proliferation and proinflammatory pathways, IL-8 modulation, and a decrease in TNF expression were the main findings reported in the included studies. Discussion: HP has shown promising effects in reducing inflammatory biomarkers in inflammatory skin diseases and experimental models of epithelial cells. Further studies should confirm this herb’s clinical significance and future applications.